Impact of Product Packaging on Sales Performance of SMEs: A Case Study of Regal Paints Uganda Limited in Namanve - Stephen Ssengendo (Uganda Christian University, 2024)
The present study was done to understand how product packaging affects the sales performance of SMEs, using Regal Paints Uganda Limited as the case study. Besides preserving the quality of the product and making its transportation easy, it communicates vital information about the product to the consumer, creates brand recognition and differentiation, and, probably, helps to influence purchasing decisions. Furthermore, packaging design is increasingly being used as a channel for developing brand messaging and fostering emotional connections with the consumer. In Uganda, as is typical of most developing countries, packaging design can become an effective marketing instrument to help SMEs in improving the survival and growth of businesses. Yet, little, if any, empirical research exists on this subject in Uganda. The paper, therefore, seeks to conduct an investigation into the impact of packaging on the sales performance of Regal paints in Uganda, based on an empirical gap in the literature, adding value to policymakers, researchers, and the company. The elaboration likelihood model posits that persuasion occurs in two routes: the central and peripheral route. The central route results in a high involvement of the individual on a particular topic; hence, the cognitive processing shall focus on evaluating message content. In contrast, the peripheral route is applied when one has low involvement in the topic and relies on more cognitive shortcuts, such as peripheral cues. Descriptive and cross-section design shall be used for the research, whereas the research methodology will be quantitative in nature. The target population size for this research is 39, while the sample size, through purposive sampling technique, has a total of 35 respondents. Major data will be collected with the help of a close ended type questionnaire consisting of statements with their respective Likert scales. SPSS software shall be utilized to analyze the gathered information to assure that it is accurate, complete, consistent, and uniform in nature. Ethical considerations will be observed in terms of principles of confidentiality, anonymity, consent, and acknowledgement of contributions from other people. Different researchers have been cited not for their contributions regarding the study. From the findings obtained, a majority of the respondents strongly agreed that when coming up with a product package, considerations of the environmental factors, rules, and regulations should be put into place by following the components of product packaging, including size, shape, color, and size.